IMPROVING THE OVERALL EFFECTIVENESS OF A TABLET PACKAGING LINE IN A PHARMACEUTICAL COMPANY - Mehtäjärvi, Jermu (My University, 2018)
This research paper focuses on introducing and analysing the main methods and tools of lean production and Six Sigma in order to improve the overall equipment effectiveness (OEE) of a specific production unit. In addition, the main emphasis of this study is not only to introduce the tools for improvement of OEE but also to examine in which circumstances the improvement of OEE increases the production performance in the most effective manner. Theoretically, the OEE rate can be increased by significantly decreasing the amount of small stops and failures in production and by enhancing the running speed of the production line. However, despite of the fact that the same theoretical development guidelines and improvement methods of lean can be applied to most companies regardless of the industry, it requires a significant amount of work to expose the production losses and non-value adding waste that must be eliminated. The empirical part of the study focused on utilizing various methods of Lean Six Sigma in order to decrease the amount of production defects from the packaging operations of a pharmaceutical company. Moreover, the study aimed to increase the overall production speed by revealing and eliminating factors preventing the machinery to operate with higher speed. Production deficiencies and challenges were analysed and revealed with various lean and Six Sigma tools, such as 5 whys root cause analysis and 80/20-rule. Systematic improvement with suitable techniques offered significant development opportunities in the production operations and enabled an increase in the effectiveness of the packaging operations. This study followed the DMAIC method and applied multiple Lean Six Sigma methods to improve the overall equipment effectiveness.
Keywords: Lean Philosophy; Six Sigma; Lean Six Sigma; Overall Equipment Effectiveness; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|